2023
DOI: 10.18002/rama.v18i1.7208
|View full text |Cite
|
Sign up to set email alerts
|

Effects and symptoms of dehydration in Brazilian jiu-jitsu athletes

Abstract: Objective. To measure rapid weight loss and urinary indicators of hydration status, as well as to assess the effects and symptoms of dehydration in Brazilian jiu-jitsu (BJJ) athletes at different moments. Methods. 17 male BJJ athletes (aged: 24.4 ± 3.5 years; body mass (BM): 76.8 ± 14.6 kg; body fat: 16.6 ± 6.4%), were evaluated between 8 and 9 am at three different moments: Baseline (10 days pre- competition), measurement of BM and stature, collection of urine samples, and food record of the previous 24 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…One of the characteristics of Brazilian jiu-jitsu competitors is that they undergo a large amount of body mass loss over a small number of days before they compete ( Brito et al, 2012 ; White and Kirk, 2021 ), representing an attempt for athletes to gain a physical advantage when competing against lighter opponents ( Barley et al, 2019 ). In Brazilian jiu-jitsu, previous studies identified that between 57% ( Brito et al, 2012 ) and 88% of male competitors reduced body mass in order to compete in a category with a lower body mass limit ( Bueno et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the characteristics of Brazilian jiu-jitsu competitors is that they undergo a large amount of body mass loss over a small number of days before they compete ( Brito et al, 2012 ; White and Kirk, 2021 ), representing an attempt for athletes to gain a physical advantage when competing against lighter opponents ( Barley et al, 2019 ). In Brazilian jiu-jitsu, previous studies identified that between 57% ( Brito et al, 2012 ) and 88% of male competitors reduced body mass in order to compete in a category with a lower body mass limit ( Bueno et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%